Answer:
The correct option is;
The inverse of the original conditional statement
Explanation:
The converse of a conditional statement is given as follows;
Conditional statement: If p then q
p → q
The converse of the conditional statement: If q then p
q → p
The contrapositive of the conditional statement: If not q then not p
~q → ~p
Therefore, the conditional statement is logically equivalent to its contrapositive
The inverse of the conditional statement: If not p, then not q
~p → ~q
Similarly
The converse of the conditional statement is equivalent to the inverse of the conditional statement.